Thread-Traction with a Sheath of Polypectomy Snare Facilitates Endoscopic Submucosal Dissection of Early Gastric Cancers - Hisatsugu Noda; Naotaka Ogasawara; Akira Koshino; Shouko Fukuta; Takuroh Nagoya; Hironori Hoshino; Kazuhiro Nagao; Tomoya Sugiyama; Yoshihiro Kondo; Yoshitsugi Ito; Shinya Izawa; Masahide Ebi; et al. (Gastroenterology Research and Practice)
Although the thread-traction (TT) method has been found useful during endoscopic submucosal dissection (ESD) for early gastric cancers, the movement of the thread interferes with the movement of the endoscope, and the lesion can only be pulled to the mouth side. We have developed the novel TT method using a sheath of polypectomy snare (TTSPS). The TTSPS method enables free and independent movement of the thread and the endoscope and allows pulling the lesion towards the anal as well as oral side. The median dissection times, numbers of instances of arterial bleeding, and numbers of local injections into the submucosal layer were significantly lower for ESD with TTSPS than for conventional ESD. Countertraction ESD using the TTSPS method is straightforward, safe, easy, noninvasive, and cost effective, and it uses instruments readily available in most hospitals to enhance visualization of cutting lines. Therefore, the TTSPS method can be universally applied in conventional ESD.